Long term safety and efficacy of ligelizumab in the treatment of Japanese patients with chronic spontaneous urticaria - Hidetoshi Takahashi; Atsushi Fukunaga; Koremasa Hayama; Takayoshi Sasajima; Ayako Fujishige; Ryohei Ichishita; Naoko Tomimatsu; Eva Hua; Vineeth Varanasi; Alis Burciu; Michihiro Hide; Thomas Severin (Allergology International)
Background: In Japan, urticaria is a common skin disorder with chronic spontaneous urticaria (CSU) being the most frequent subtype. This study evaluated the safety of ligelizumab (anti-IgE monoclonal antibody) in Japanese CSU patients. Methods: This was a Phase 3 multicenter, open-label, single-arm 52-week study in adult Japanese patients with CSU inadequately controlled with locally approved doses of H1-antihistamines. The primary objective reported the safety of ligelizumab 120 mg subcutaneously every 4 weeks, by evaluation of treatment emergent adverse events (TEAE). Secondary objectives evaluated efficacy by absolute change from baseline (CFB) in weekly urticaria activity score (UAS7), and the proportion of patients with UAS7 = 0, and dermatology life quality index (DLQI) = 0–1 over time. Results: From a total of 66 CSU patients (80.3% females; mean ± SD age 46.4 ± 13.2 years; mean ± SD baseline UAS7 28.7 ± 6.5) enrolled, 53 patients (80.3%) reported ≥1 TEAE during the study, with no severe or serious adverse events, no anaphylaxis events and low frequency of TEAEs leading to treatment discontinuations (6.1%). Absolute mean CFB of UAS7 showed a rapid onset of response at Week 4 (−14.2) with further improvement until end of treatment at Week 52 (−22.9). The proportion of patients achieving UAS7 = 0 improved over time (14.5% at Week 4; 50.0% at Week 52). A sizable proportion of patients achieved DLQI 0–1 with the first dose of ligelizumab (38.5%), and improvements observed throughout the study until Week 52 (68.8%). Conclusions: Treatment with ligelizumab 120 mg was well-tolerated with mild to moderate adverse events and was efficacious in Japanese patients.